2009
DOI: 10.1308/003588409x432112
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Skin Lesions by Trainee Surgeons: Experience Improves Accuracy

Abstract: Ann RC oll Surg Engl 2009; 91:4 94-499 494The UK Government's restructuring of specialist training,outlinedinModernising Medical Careers (MMC), 1 will have asignificanti mpact on surgical training in all surgical specialties including plastic surgery.Frequent evaluationofboth the surgical and diagnostic skills of traineesw ill be needed to determine the impact of shortened specialisttraining.Skin lesions make up alarge part of the plastic surgeon's out-patient workload and one of the effectso ft he Government'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In other areas of dermatology, increased training and experience have been shown to improve diagnostic accuracy. [28][29][30][31] We suspect that with increased familiarity, concordance and reliability will improve similarly when inpatient consultative teledermatology is studied further. It will also be important to examine the impact of increased contact with the primary team, including potential for follow-up.…”
mentioning
confidence: 99%
“…In other areas of dermatology, increased training and experience have been shown to improve diagnostic accuracy. [28][29][30][31] We suspect that with increased familiarity, concordance and reliability will improve similarly when inpatient consultative teledermatology is studied further. It will also be important to examine the impact of increased contact with the primary team, including potential for follow-up.…”
mentioning
confidence: 99%
“…Out of 59 patients of fungal infections, most of them were of Dermatophytoses (51), and few of Onychomycosis (8). Out of 20 patients of bacterial infections, maximum were of folliculitis (13), few of impetigo (4) and carbuncle (3). In viral infections, from 26 patients, most of them were of Herpes zoster (6), Molluscumcontagiosum(6), Viral warts (6), Chicken pox (4) and Herpes labialis (4).…”
Section: Resultsmentioning
confidence: 99%
“…In other areas of dermatology, increased training and experience have been shown to improve diagnostic accuracy with teledermatology. 1,[10][11][12][13] Thomas J suggested that after initial face-to-face or tele consultation, it becomes very easy for the patient as well as the doctor who can have a followup through tele-consultation, which apart from saving time and travel ensures best outcome of the treatment. 14 Tan E et al also suggested that making diagnoses with images alone is challenging, and additional multimodal communication is likely important.…”
Section: Discussionmentioning
confidence: 99%
“…Registrar inexperience is likely a large component that has attributed to our margin rate. Clinical experience has been shown to be a significant factor influencing diagnostic accuracy for skin lesions in trainee surgeons, 17 and it has been shown that consultants display significantly greater sensitivity and positive predictive value for diagnosing malignant skin lesions 18,19 . A lack of experience can lead to difficulty discerning the border between malignant and normal skin and might also cause concern for poor cosmetic result, difficulty with wound closure or even breaching of the anaesthetic field.…”
Section: Discussionmentioning
confidence: 99%